(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. This study was designed to compare an antidepressant medication, citalopram, with psychological training in hemodialysis patients with symptoms of anxiety and depression. Materials and Methods. A total number of 44 hemodialysis patients scored 8 and more on the Hospital Anxiety and Depression Scale (HADS) were randomly allocated to two groups to receive citalopram, 20 mg/d, for 3 months or to attend 6 sessions of 1-hour psychological training. A nephrologist and a senior psychiatry resident were responsible for training of the patients, which contained explaining the anatomy of the kidneys, causes of kidney failure, treatment modalities, the mechanism involved in hemodialysis, the required care in hemodialysis patients, stages of adaptive reaction in human, and techniques of problem solving, stress management, and muscle relaxation. Both groups completed the HADS once before and once after the treatment. The final results of the two groups were compared. Results. Citalopram administration led to a significant decrease in the patients’ depression score (P = .001), anxiety score (P = .048), and total HADS score (P = .002). Psychological training sessions also decreased significantly depression (P = .04), anxiety (P = .03), and total HADS scores (P = .045). There was no significant difference in the amount of decrease in the scores of depression (P = .65), anxiety (P = .19), and the total HADS (P = .66) between the two groups. Conclusions. Psychological training and citalopram have similar effects on improving the symptoms of anxiety and depression in hemodialysis patients.